2017
DOI: 10.1177/0886260517708762
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents at Serious Psychosocial Risk: What Is the Role of Additional Exposure to Violence in the Home?

Abstract: Research into the effects of interpartner violence on the psychosocial development of the children of maltreated mothers is a relatively new field. This work examines the impact of exposure to interpartner violence (EIPV) on minors in middle and late adolescence, where this vicarious maltreatment is in addition to other situations of severe psychosocial risk. A group of adolescents who had suffered various types of direct maltreatment were compared with another group who, in addition to experiencing direct mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…The final studies, when combined, had a total sample size of 2,546 children (Mean age = 12.70, SD = 3.30), that ranged across countries (including a mixture of HICs and LMICs), with the measure being translated and administered into several languages. This includes Sweden ( 48 , 57 , 58 ), India ( 51 ), Spain ( 56 ), Brazil ( 50 ), Iraqi-Kurdistan ( 53 ), Pakistan ( 54 ), South Africa ( 55 ) and Iran ( 52 ). Despite being translated into different languages for implementation in different countries and contexts, internal consistency remained when utilizing the CEDV with diverse populations, and the results indicated that the CEDV demonstrated content, convergent, and discriminant validity ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…The final studies, when combined, had a total sample size of 2,546 children (Mean age = 12.70, SD = 3.30), that ranged across countries (including a mixture of HICs and LMICs), with the measure being translated and administered into several languages. This includes Sweden ( 48 , 57 , 58 ), India ( 51 ), Spain ( 56 ), Brazil ( 50 ), Iraqi-Kurdistan ( 53 ), Pakistan ( 54 ), South Africa ( 55 ) and Iran ( 52 ). Despite being translated into different languages for implementation in different countries and contexts, internal consistency remained when utilizing the CEDV with diverse populations, and the results indicated that the CEDV demonstrated content, convergent, and discriminant validity ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…The test-retest reliability has shown that the CEDV scale is consistent over time and has indicated a positive correlation in convergent validity testing with other validated questionnaires, namely, the ‘Things I have seen and heard’ and the ‘Exposure to physical aggression’ questionnaire ( 13 ). Moreover, existing studies also demonstrated concurrent validity between CEDV scale and several outcomes related to exposure to domestic violence such as anxiety symptoms, maladjustment, reduced self-esteem and physical health complaints ( 11 , 14 , 15 ).…”
Section: Methodsmentioning
confidence: 92%
“…Existing studies have reported that the CEDV scale is reliable among diverse populations internationally with relatively high overall Cronbach’s coefficients, ranging from 0.79 to 0.97 ( 11 , 12 ). Similarly, the translated version of the CEDV scale demonstrated a good level of internal consistency, with α coefficients ranging from 0.74 to 0.89 ( 13 15 ). The test-retest reliability has shown that the CEDV scale is consistent over time and has indicated a positive correlation in convergent validity testing with other validated questionnaires, namely, the ‘Things I have seen and heard’ and the ‘Exposure to physical aggression’ questionnaire ( 13 ).…”
Section: Methodsmentioning
confidence: 95%
“…In another sense, there are several protective factors that allow reducing the risk of suicide risk, acting as insulators against it, such as self-esteem [21,43], reasons for living [28], and satisfaction with social support [14,21]. According to the results obtained, at-risk adolescents showed higher self-esteem compared to not-at-risk adolescents, which contradicts the tendency for low self-esteem in this type of population [42].…”
Section: Discussionmentioning
confidence: 98%